The Effect of Entrepreneurial Orientation, Market Orientation and Project Manajement Perspectives on Competitive Adventage in Order to Improve Business Performance (The Study on Property Companies in Pati) - Putra, Momahad Wahyudi; Raharjo, Susilo Toto (Budapest International Research and Critics University, 2021)
The purpose of this study is to examine and analyze the effect of entrepreneurial orientation, market orientation and project management perspective on competitive advantage and property business performance in Pati Regency. This research is a regression and quantitative research. This research was conducted at the end of 2021 on property companies in Pati Regency with a total of 50 property companies. Data collection using a closed questionnaire, and data analysis using analysis technique partial least squares (PLS). The results showed that entrepreneurial orientation, market orientation, management perspective had a positive effect on competitive advantage. Entrepreneurial orientation, market orientation, management perspective and competitive advantage have a positive effect on business performance. The conclusion is that entrepreneurial orientation, market orientation, management perspective play an important role in competitive advantage and property business performance in Pati district.